Hyperprogression After Immune-Checkpoint Inhibitor Treatment: Characteristics and Hypotheses - Zang, Hongjing; Peng, Jinwu; Zheng, Hongmei; Fan, Songqing (Frontiers in Oncology, 2020)
Immunotherapies in tumors have attracted increasing attention. They play an important role in precision medicine. Many ICIs (immune-checkpoint inhibitor) have obtained FDA approval and show good performance in the clinic. Hyperprogressive disease (HPD) after ICIs was first described in November 2016. Since then, a series of cases of HPD after ICIs have been reported. Notwithstanding that only a small subset of patients may experience this atypical response, HPD in affected patients means shorter survival time and worse prognosis. We summarized common standards for HPD diagnosis and profiled advantages and disadvantages. Elderly age, MDM2 family amplification, infiltration of PD-1-positive regulatory effector T cells and M2-like macrophages and cancer stem cells may take part in HPD occurrence. Overall, we should focus on investigating the early markers and pathogenic mechanisms of HPD to solve this issue of ICIs.